A genotype-controlled analysis of plasma dopamine β-hydroxylase in healthy and alcoholic subjects: evidence for alcohol-related differences in noradrenergic function - Köhnke, Michael D; Zabetian, Cyrus P; Anderson, George M; Kolb, Werner; Gaertner, Ines; Buchkremer, Gerhard; Vonthein, Reinhard; Schick, Sandra; Lutz, Ulrich; Köhnke, Annette M; Cubells, Joseph F (Biological psychiatry (1969), 2002)
Norepinephrine and dopamine mediate important aspects of alcoholism and alcohol withdrawal. Dopamine-β-hydroxylase (DβH) converts dopamine to norepinephrine. A recent study demonstrated a strong association between variance in plasma DβH activity and a novel polymorphism (DBH-1021C→T) at the structural locus (DBH) encoding DβH protein. Our study investigated whether the DBH-1021C→T polymorphism and plasma DβH activity were associated with alcoholism or with delirium tremens (DT) during alcohol withdrawal by analyzing 207 German alcoholic and 102 healthy control subjects. We also examined the influence of the polymorphism on enzyme activity. Mean (+SD) plasma DβH activity measured in alcoholic subjects abstinent was significantly lower than that observed in control (27.7 + 16.7 vs. 35.6 + 18.8; p = .01). It did not differ between subjects with DT during withdrawal and subjects with mild withdrawal symptoms. The T allele of the DBH-1021C→T polymorphism was significantly associated with lower plasma DβH activity. None of the alleles or genotypes were associated with alcoholism or DT. The data indicate that the alcoholism-related reduction in plasma DβH activity is independent of genotype at DBH-1021C→T and replicate the finding that DBH-1021C→T is strongly associated with plasma DβH activity in a native Western European population.